Response of poly-phosphate accumulating organisms to free nitrous acid inhibition under anoxic and aerobic conditions - Zhou, Yan (2013)
The response of free nitrous acid (FNA)-adapted poly-phosphate accumulating organisms (PAOs) to FNA inhibition under aerobic and anoxic conditions was studied. Anoxic P-uptake was 1–6 times more sensitive to the inhibition compared to aerobic P-uptake. The aerobic nitrite reduction rate increased with FNA concentration, accompanied by an equivalent decrease in the oxygen uptake rate, suggesting under high FNA concentration conditions, electrons were channeled to nitrite reduction from oxygen reduction. In contrast, the nitrite reduction rate decreased with increased FNA concentration under anoxic conditions. Anaerobic metabolism of PAO under both anoxic and aerobic conditions was observed at high FNA concentrations. Growth of PAOs decreased sharply with FNA concentration and stopped completely at FNA concentration of 10 μg HNO2–N/L. This study, for the first time, investigated the function of nitrite/FNA in an aerobic denitrifying phosphate removal process by evaluating electron as well as energy balances, and provides explanation for FNA inhibition mechanisms.